2018
DOI: 10.1556/2006.7.2018.88
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the Persian Internet Disorder Scale among adolescents

Abstract: Background and aimsGiven the growing epidemiological research interest concerning Internet addiction, brief instruments with a robust theoretical basis are warranted. The Internet Disorder Scale (IDS-15) is one such instrument that can be used to quickly assess the Internet addiction in an individual. However, only two language versions of the IDS-15 have been developed. This study translated the IDS-15 into Persian and examined its psychometric properties using comprehensive psychometric testing.MethodsAfter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 58 publications
(92 reference statements)
3
21
0
Order By: Relevance
“…That is, the good properties of the SBS are not influenced by the samples (aka being sample free). Also, the DIF findings in Rasch models demonstrated the appropriateness to compare the SBS item scores between Iranian and Afghanistani samples (Lin et al 2018b).…”
Section: Discussionmentioning
confidence: 94%
“…That is, the good properties of the SBS are not influenced by the samples (aka being sample free). Also, the DIF findings in Rasch models demonstrated the appropriateness to compare the SBS item scores between Iranian and Afghanistani samples (Lin et al 2018b).…”
Section: Discussionmentioning
confidence: 94%
“…28 A higher acceptance and a lower standard error of measurement indicate better psychometric properties. 29 Moreover, factor loading higher than 0.4; average variance extracted higher than 0.5, and composite reliability higher than 0.6 are in anticipation. 29…”
Section: Methodsmentioning
confidence: 93%
“…For CFA, a nonsignificant χ 2 test, a comparative fit index (CFI) >0.9, a Tucker-Lewis index (TLI) >0.9, a root mean square error of approximation (RMSEA) <0.08, and a standardized root mean square residual (SRMR) <0.08 support the single-factor structure for SDM-Q-9 or SDM-Q-Doc. 28 For internal consistency, Cronbach’s α is expected to be higher than 0.7 29 ; for corrected item-total correlation and test-retest reliability, values are expected to be higher than 0.4. 28 A higher acceptance and a lower standard error of measurement indicate better psychometric properties.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, technological addictions such as social media addiction can have negative and severe psychological and psychosocial impacts (Griffiths, 2000). The excessive online use is typically accompanied by a reduction in the size of the individuals' social circle, as well as an increase in loneliness and depression (Lin et al, 2018). The results of the study by Yao and Zhong (2014) using a prospective study confirmed that excessive and unhealthy use of the Internet over time increased the sense of loneliness among male and female students (aged: 18-36 years).…”
Section: Introductionmentioning
confidence: 99%